TEORI BELAJAR DAN IMPLIKASINYA DALAM PENDIDIKAN AGAMA ISLAM : Kajian Konseptual terhadap Proses Pembelajaran - Turmidzi, Imam; Rohadi, Rohadi; Mahmud, Faizul (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Learning theories play a crucial role in shaping an effective Islamic Religious Education (PAI) learning process. However, PAI learning practices often emphasize cognitive aspects and neglect the integration of learning theories that support holistic student development. This study aims to examine learning theories and apply them to Islamic Religious Education (PAI) learning. This study employed a qualitative descriptive approach with a library research method. Data were collected through analysis of books, academic journals, and relevant scientific papers related to learning theories and Islamic education. The research findings indicate that behaviorist, cognitive, constructivist, and humanistic learning theories have complementary roles in Islamic Religious Education (PAI) learning. Behaviorist theories support the habituation of religious practices, cognitive theories strengthen understanding and reasoning, constructivist theories promote contextual learning, and humanistic theories develop religious awareness and character. This study concludes that the integration of various learning theories contributes to meaningful, holistic, and value-based PAI learning that aligns with the goals of Islamic education.